Gut bacteria recycle uric acid nitrogen in termites: A strategy for nutrient conservation - Potrikus, Catherine J. (1981)
Reticulitermes flavipes termites synthesize uric acid via purine-nucleoside phosphorylase (purine-nucleoside: orthophosphate ribosyltransferase, EC 2.4.2.1) and xanthine dehydrogenase (xanthine:NAD(+) oxidoreductase, EC 1.2.1.37), but their tissues lack uricase (urate:oxygen oxidoreductase, EC 1.7.3.3) or any other enzyme that degrades uric acid. Nevertheless, uricolysis occurs in termites, but as an anaerobic process mediated by hindgut bacteria. (14)C-Tracer experiments showed that termites transport uric acid from the site of synthesis and storage (fat body tissue) to the site of degradation (hindgut microbiota) via Malpighian tubules. Moveover, [1,3-(15)N]uric acid dissimilated by gut bacteria in vivo leads to assimilation of (15)N into termite tissues. NH(3), a product of uricolysis, is a potential N source for termites, either directly via glutamine synthetase [L-glutamate:ammonia ligase (ADP-forming), EC 6.3.1.2] activity of fat body tissue or indirectly through microbe assimilation. Symbiotic recycling of uric acid N appears to be important to N conservation in these oligonitrotrophic insects.